GESTÃO INTEGRADA DE MICOTOXINAS NA CADEIA PRODUTIVA DO MILHO DESTINADO À ALIMENTAÇÃO DE FRANGOS DE CORTE NO BRASIL - Brabet, Catherine; Salay, Elisabete; Freitas-Silva, Otniel; Florindo Alves, Alexandre; Machinski Jr., Miguel; Azevedo Vargas, Eugenia; Zakhia-Rozis, Nadine (Cadernos de Ciência & Tecnologia, 2005)
Este artigo descreve as atividades de pesquisa realizadas no Brasil, no âmbito do projeto de cooperação INCO-DEV Mycotox, financiado pela Comissão Européia (ICA4-CT-2002-10043). Esse projeto visa ao desenvolvimento de um Sistema de Gestão Integrada da Qualidade (SGIQ) para o controle das micotoxinas nas cadeias de trigo e de milho dos países do Cone Sul da América Latina (Brasil, Chile, Argentina e Uruguai). A metodologia escolhida consiste em aplicar os princípios da Hazard Analysis Critical Control Point (HACCP) ao longo das cadeias produtivas, no âmbito de estudos de casos realizados nos países do Cone Sul que são parceiros do projeto, apoiando-se em dupla abordagem: técnica e socioeconômica. O projeto também propõe o desenvolvimento e a validação de métodos de análise de micotoxinas. A cadeia de milho para a alimentação de frangos de corte foi selecionada para o estudo de caso no Brasil, por ser esse país o terceiro produtor mundial de milho e por ser o setor avícola o primeiro consumidor da produção nacional. O SGIQ desenvolvido terá um caráter genérico e poderá ser aplicado a outros critérios de qualidade e/ou a outras cadeias produtivas.Termos para indexação: micotoxinas, milho, alimentação animal, frangos, Brasil, gestão da qualidade.INTEGRATED MYCOTOXIN MANAGEMENT IN THE BRAZILIAN CORN CHAIN FOR POULTRY FEED ABSTRACTThis article presents the research activities carried out in Brazil within the framework of the INCO-DEV Mycotox project. This co-operation project funded by the European Commission (ICA4-CT-2002-10043) aims at developing an integrated quality management system for the control of mycotoxins in the corn and wheat production chains in Latin America South Cone countries (Brazil, Chile, Argentina, and Uruguay). The project involves institutional partners as well as key actors of the cereal production chains. The approach chosen consists in applying the HACCP (Hazard Analysis Critical Control Point) principles to the entire agri-food chain within the framework of case studies carried out in the South Cone countries involved in the project, taking into account not only the technical issues but also the socio-economic issues. This approach will help validate and implement technical and organizational itineraries adapted to the local contexts for controlling mycotoxin contamination. In addition, the activities emphasise the development and validation of effective analytical methods for mycotoxin determination (chromatographic methods, alternative techniques such as near infrared spectrometry and the mini-column-based Toximet procedure for routine on-field assessment). Brazil is the third largest corn producer in the world. More than 70% of the national production is used for animal feed, most of which poultry. This is the reason why the corn production chain for poultry feed was selected as the case study to be conducted in this country. The integrated quality management system developed will be generic, and will be able to apply to other quality criteria and/or agri-food chains.Index terms: animal feeding, quality management, vegetal production, tools and methods.MAÎTRISE DES MYCOTOXINES DANS LA FILIÈRE MAÏS AU BRÉSILRÉSUMÉ Cet article présente les activités de recherche menées au Brésil dans le cadre du projet INCO-DEV Mycotox. Ce projet de coopération, financé par la Commission Européenne (ICA4-CT-2002-10043), vise le développement d'un système de gestion intégrée de la qualité (SGIQ) pour la maîtrise des mycotoxines dans les filières blé et maïs des pays du Cône sud d'Amérique Latine (Brésil, Chili, Argentine et Uruguay). La démarche choisie consiste à appliquer les principes de l'HACCP (Hazard Analysis Critical Control Point) à l'ensemble de la filière dans le cadre d'études de cas réalisées dans les pays du Cône sud partenaires du projet, en s'appuyant sur une double approche technique et socioéconomique. L'accent est mis également sur le développement et la validation de méthodes d'analyse des mycotoxines. Le Brésil étant le troisième producteur mondial de maïs et le secteur avicole le premier consommateur de la production nationale, la filière maïs pour l'alimentation des poulets de chair a été retenue pour l'étude de cas dans ce pays. Le SGIQ développé aura un caractère générique et pourra s'appliquer à d'autres critères de qualité et/ou filières.Termes d'indexation: productions végétales, méthodes et outils, alimentation animale, gestion de la qualité.